Implementasi Pendidikan Inklusif dengan Isu Kesenjangan Akses dan Tren - Mustopa, Ahmad Ali; J, Jumriani; R, Rosdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Inclusive education is an educational approach that aims to provide equal learning opportunities for all students, including those with special needs. However, the implementation of inclusive education in various regions still faces major challenges, especially related to the gap in access and differences in policy trends. This study aims to explore the factors that influence the implementation of inclusive education in Indonesia and analyze the various obstacles faced by educational institutions in creating a friendly and equal learning environment. Using a qualitative approach, data were collected through literature studies. The results of the study indicate that the gap in access to educational facilities and infrastructure, the lack of trained educators, social strata and differences in understanding related to the concept of inclusion are the main factors that hinder the implementation of inclusive education. In addition, inconsistent education policy trends in various regions worsen this situation. Therefore, collaboration between the government, schools, and the community is needed to create a more inclusive and equitable education system. This study is expected to contribute to formulating effective and sustainable inclusive education policy strategies in the future.